Calculation of Areas Possible and Width Predicted Chemical Contamination Using Object-oriented Programming Environment - Boryk, V. (Physics and Chemistry of Solid State, 2019)
A code in Visual Basic Application environment for MS Office, which automates the calculation of the area of the zone of possible chemical contamination in accidents on chemically hazardous objects the diversion of chemically hazardous substances.